Pengembangan dan Penerapan Media Audiovisual dalam Peningkatan Pengetahuan Ibu Balita Mengenai Kenaikan Berat Badan pada Balita - Hastuti, Agnia Winda; Muwakhidah, Muwakhidah (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
Nutritional problems remain a major challenge in Indonesia, especially among children under the age of five. One of the most common issues is malnutrition and insufficient weight gain in young children. This is often caused by a lack of knowledge among parents—particularly mothers—about how to properly monitor their child’s growth. Engaging and easy-to-understand educational tools, such as audiovisual media, are believed to be effective in improving awareness and understanding of the importance of tracking a child’s weight gain. This study aims to develop and implement audiovisual media as an educational tool to enhance mothers’ knowledge regarding weight gain in children under five years old. The study employed a Research and Development (R&D) approach, which included stages of analysis, planning, development, and implementation. The validation process involved material experts, media experts, and the target users—mothers of young children. The main focus of this research was the development of an educational audiovisual video. Validation results showed that the developed media was considered feasible, with an average expert rating of 3.9. The Content Validity Index (CVI) reached a perfect score of 1.0, indicating unanimous agreement among experts on the relevance of the material. Implementation of the media demonstrated an increase in participants’ knowledge, with the average score improving from 54.6 on the pre-test to 88 on the post-test. The developed audiovisual media proved to be effective in enhancing mothers’ understanding of weight gain in young children. This type of media can serve as an engaging and accessible alternative for nutrition education.